Relationship between Phenolic Compounds and Antioxidant Activity in Berries and Leaves of Raspberry Genotypes and Their Genotyping by SSR Markers - Vadim G. Lebedev; Tatyana N. Lebedeva; Elena O. Vidyagina; Vladimir N. Sorokopudov; Anna A. Popova; Konstantin A. Shestibratov (MDPI AG, 2022)
The red raspberry is one of the world's most popular berries. The main direction of its breeding has switched to nutritional quality, and the evaluation of raspberry germplasm for antioxidant content and activity is very important. As berries, raspberry leaves contain valuable bioactive compounds, but the optimal time for their collection is unknown. We evaluated 25 new breeding lines and standard raspberry cultivars for their polyphenolic content and antioxidant capacity. The antioxidant activity of berries correlated better with the content of total phenolics (0.88 and 0.92) and flavonoids (0.76 and 0.88) than with anthocyanins (0.37 and 0.66). Two breeding lines were significantly superior to the standard cultivars and can be used in further breeding. Leaves collected in three phenological phases of the raspberry contained more phenolics (5.4-fold) and flavonoids (4.1-fold) and showed higher antioxidant activities (2.4-fold in FRAP assay, 2.2-fold in ABTS) than berries. The optimal time for harvesting raspberry leaves is the fruit ripening stage, with exceptions for some cultivars. Genetic diversity analysis using microsatellite (SSR) markers from flavonoid biosynthesis genes divided the genotypes into five clusters, generally in agreement with their kinships. The relationship between genetic data based on metabolism-specific SSR markers and the chemical diversity of cultivars was first assessed. The biochemical and genetic results show a strong correlation (0.78). This study is useful for further the improvement of raspberry and other berry crops.